Commentary on Poema(s) da cabra and Comendadores jantando by Joao Cabral de Melo Neto - Miyazaki, Tieko Yamaguchi [UNESP]; Macedo, Ricardo Marques (Univ Estadual Paulista, Fundacao Editora Unesp, 2020)
The article is inspired by two concepts by Algirdas Julien Greimas in the analysis of poems by Joao Cabral de Melo Neto (Poema(s) da cabra; Comendadores jantando). First in the concept of fracture of the work L' imperfection (1987), when examining as the capture of the real through the seeing in the search for what would be beyond the surface of the opinion. Second, in the concept of poetic language understood as one in which redundancy enriches the selected contents, due to the paradigmatic organization of the substance, both of content and expression.
Keywords: Fracture; Guizzo; Imperfection; Metalinguistics; Paradigmatic organization